Foot and mouth disease in Iraq: strategy and control - Mahdi, Ali Jafar (Kansas State University, 2010)
Foot-and-mouth disease (FMD) is a highly infectious viral disease of cattle, pigs, sheep, goats, buffalo, and artiodactyl wildlife species. Foot-and-mouth disease virus is endemic and periodic devastating epidemics have occurred and caused heavy economic losses in Iraq for a long time. The first official cases of FMD were recorded in 1937, while the first record of a specific FMD serotype in Iraq was serotype A in 1952. Other serotypes have been reported since then; serotypes O, SAT-1 and Asia1 were recorded in 1957, 1962, and 1975, respectively. Veterinary Services in Iraq has been severely weakened over the past two decades, and its infrastructure has been devastated as a consequence of previous political conflicts, wars and international sanctions. The breakdown of Veterinary Services led to the disruption of disease control strategies, collapse of disease surveillance and monitoring, and weakening of response systems. The destruction of the Al-Dora FMD laboratories for diagnosis and vaccine production by the United Nation in 1996, and the restrictions placed on the importation of vaccines have strongly affected the FMD control program. A severe epidemic of FMD occurred in Iraq in 1998, affecting 2.5 million ruminants and causing heavy losses in newly born animals. It is estimated to have killed about 550,000 animals. The outbreak was due to the serotype O1 Middle East strain which has affected large and small ruminants. In 2009, Iraq was severely affected by new serotype A (subtype A Iran 05). The major efforts of Veterinary Services in Iraq have been directed towards control of FMD by vaccination strategies. Two types of vaccine have been used, trivalent vaccine (O, A 22, and Asia 1) for cattle and buffalo and monovalent vaccine (O Manisa) for sheep and goats. Vaccination has been implemented once yearly on a voluntary basis. Sometimes other limited control measures have accompanied vaccination, which include quarantine, movement control, focused vaccination, disinfection, and public awareness programs. The FMD control program in Iraq has been confronted by many challenges: deficits in FMD surveillance and emergency preparedness, limited diagnostic capabilities, difficulties in restricting animal movement, and lack and irregular supply of appropriate vaccines.
Keywords: FMD; Iraq; Biology, Veterinary Science (0778)